Synthesis of 12-Membered Tetra-aza Macrocyclic Pyridinophanes Bearing Electron-Withdrawing Groups - Yepremyan, Akop (J Org Chem, 2020)
The number of substituted pyridine pyridinophanes found in the literature is limited due to challenges associated with 12-membered macrocycle and modified pyridine synthesis. Most notably, the electrophilic character at the 4-position of pyridine in pyridinophanes presents a unique challenge for introducing electrophilic chemical groups. Likewise, of the few reported, most substituted pyridine pyridinophanes in the literature are limited to electron-donating functionalities. Herein, new synthetic strategies for four new macrocycles bearing the electron-withdrawing groups CN, Cl, NO(2), and CF(3) are introduced. Potentiometric titrations were used to determine the protonation constants of the new pyridinophanes. Further, the influence of such modifications on the chemical behavior is predicted by comparing the potentiometric results to previously reported systems. X-ray diffraction analysis of the 4-Cl substituted species and its Cu(II) complex are also described to demonstrate the metal binding nature of these ligands. DFT analysis is used to support the experimental findings through energy calculations and ESP maps. These new molecules serve as a foundation to access a range of new pyridinophane small molecules and applications in future work.